Boron Incorporation in Silicate Melt: Pressure-induced Coordination Changes and Implications for B Isotope Fractionation - Drewitt, James W. E.; Bromiley, Geoffrey D. (Frontiers in Earth Science, 2022)
Ab initio molecular dynamics simulations have been employed to investigate the nature of boron incorporation in a model basaltic melt composition at pressures up to 8 GPa. At ambient pressure, boron is predominantly incorporated as trigonal planar BO3 units. With increasing pressure, the proportion of tetrahedral BO4 increases markedly in parallel with increases in the coordination of other cations in silicate liquids. In contrast to studies of high pressure boron-rich silicate glasses and liquids where boron units are polymerized, simulations of low B-concentration liquid here indicate that boron does not adopt a significant role as a network-forming cation. Marked changes in the proportion of BO4 in silicate melt at even moderate pressures (from 5 to 20%, over the pressure range 0 to 3 GPa) imply that pressure may significantly affect the extent of melt/fluid and melt/crystal boron isotope fractionation. This pressure-effect should be considered when using boron isotope data to elucidate processes occurring within the mantle.